Total Synthesis, Stereochemical Assignment, and Field‐Testing of the Sex Pheromone of the Strepsipteran Xenos peckii. Issue 18 (22nd March 2016) - Zhai, Huimin; Hrabar, Michael; Gries, Regine; Gries, Gerhard; Britton, Robert
Abstract: The sex pheromone of the endoparasitoid insect Xenos peckii (Strepsiptera: Xenidae) was recently identified as (7 E, 11 E )‐3, 5, 9, 11‐tetramethyl‐7, 11‐tridecadienal. Herein we report the asymmetric synthesis of three candidate stereostructures for this pheromone using a synthetic strategy that relies on an sp 3 –sp 2 Suzuki–Miyaura coupling to construct the correctly configured C7‐alkene function. Comparison of 1 H NMR spectra derived from the candidate stereostructures to that of the natural sex pheromone indicated a relative configuration of (3 R*, 5 S*, 9 R* ). Chiral gas chromatographic (GC) analyses of these compounds supported an assignment of (3 R, 5 S, 9 R ) for the natural product. Furthermore, in a 16‐replicate field experiment, traps baited with the synthetic (3 R, 5 S, 9 R )‐enantiomer alone or in combination with the (3 S, 5 R, 9 S )‐enantiomer captured 23 and 18 X. peckii males, respectively (mean±SE: 1.4±0.33 and 1.1±0.39), whereas traps baited with the synthetic (3 S, 5 R, 9 S )‐enantiomer or a solvent control yielded no captures of males. These strong field trapping data, in combination with spectroscopic and chiral GC data, unambiguously demonstrate that (3 R, 5 S, 9 R, 7 E, 11 E )‐3, 5, 9, 11‐tetramethyl‐7, 11‐tridecadienal is the X. peckii sex pheromone. Abstract : Cryptic insect with potent signal : The sex pheromone of the endoparasitoid insect Xenos peckii (Strepsiptera: Xenidae) was recently identified as (7 E, 11 E )‐3 R, 5 S, 9 R 11‐tetramethyl‐7, 11‐tridecadienal (see structure). Here the asymmetric synthesis of three candidate stereostructures for this pheromone is reported using a synthetic strategy that relies on an sp 3 –sp 2 Suzuki–Miyaura coupling to construct the correctly configured C7‐alkene function (see figure).